The analysis of DNA interstrand cross-links and their repair by the modified comet assay - Castle, L; Swift, LP; McHugh, P (Humana Press, 2020)
DNA interstrand cross-links (ICLs) are an extremely toxic form of DNA damage that cells experience upon exposure to natural metabolites. Moreover, ICLs are cytotoxic lesions produced by a range of clinically important anticancer agents. Therefore, improving our understanding of ICL induction and processing has important implications in biology and medicine. The sensitive detection of ICLs in mammalian cells is challenging but has been aided by the development of a modified form of the single-cell gel electrophoresis (SCGE) assay, also known as the “comet assay.” Here we describe this method and how it can be used to sensitively monitor the induction and removal of ICLs in single mammalian cells.